2023
DOI: 10.3390/pharmaceutics15051480
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Fisetin-Encapsulated β-Cyclodextrin Nanosponges for Breast Cancer

Alaa R. Aboushanab,
Riham M. El-Moslemany,
Amal H. El-Kamel
et al.

Abstract: Fisetin (FS) is considered a safer phytomedicine alternative to conventional chemotherapeutics for breast cancer treatment. Despite its surpassing therapeutic potential, its clinical utility is hampered by its low systemic bioavailability. Accordingly, as far as we are aware, this is the first study to develop lactoferrin-coated FS-loaded β-cyclodextrin nanosponges (LF-FS-NS) for targeted FS delivery to breast cancer. NS formation through cross-linking of β-cyclodextrin by diphenyl carbonate was confirmed by F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Moreover, loading FS into NS (nanosponges) resulted in a significant decrease in Bcl-2 levels along with increased expression of the Bax gene compared to FIS alone. All therapies significantly increased the expression of the caspase-3 gene, confirming the involvement of the apoptotic process in the anti-tumor activity of FIS [167]. To determine the effectiveness of the in vivo combination therapy of FIS and gemcitabine, researchers utilized mice with an orthotopic pancreatic cancer allografts.…”
Section: Fisetinmentioning
confidence: 91%
“…Moreover, loading FS into NS (nanosponges) resulted in a significant decrease in Bcl-2 levels along with increased expression of the Bax gene compared to FIS alone. All therapies significantly increased the expression of the caspase-3 gene, confirming the involvement of the apoptotic process in the anti-tumor activity of FIS [167]. To determine the effectiveness of the in vivo combination therapy of FIS and gemcitabine, researchers utilized mice with an orthotopic pancreatic cancer allografts.…”
Section: Fisetinmentioning
confidence: 91%
“…In vitro studies conducted by Aboushanab et al confirmed that LF-FS-NS increased cytotoxicity toward breast cancer cells without impacting normal cells. Moreover, in a breast cancer mouse model, LF-FS-NS exhibited higher bioavailability and targeting and significantly inhibited tumor growth by inducing apoptosis (Aboushanab et al, 2023). This innovative NDDS offers several benefits, notably high FST loading and entrapment efficiency, extended release, and augmented anticancer efficacy of FST through both passive targeting via enhanced permeability and retention effect and active targeting via LF coating.…”
Section: Fisetinmentioning
confidence: 96%